Analisis Pengaruh Kualitas Produk dan Faktor Harga terhadap Keputusan Pembelian Sebuah Studi Kasus - Leonora Puspa (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The research aims to determine the influence of product quality on consumer purchasing decisions at the Hawai Bakery Agen Merauke outlet. (2) To determine the influence of price on consumer purchasing decisions at the Hawai Bakery Agen Merauke outlet. (3) The approach taken in this research uses a quantitative research approach and the population in this research is 4,757 with a research sample of 94 people. The research results show that product quality partially has a positive and significant effect on purchasing decisions, price partially has a positive and significant effect on purchasing decisions. This is proven by the calculated t value being greater than the t table value, namely 2.600 > 1.985 with a significant level of 0.011 < 0.05 for the purchasing decision variable and a value of 10.615 > 1.985 for the price variable with a significant level of 0.000 < 0.05